Multiple Hypermetabolic Subcutaneous Lesions From Hidradenitis Suppurativa Mimicking Metastases on 18F-FDG PET/CT. (January 2018) - Asamoah, Philip; Wale, Daniel J.; Viglianti, Benjamin L.; Wong, Ka Kit; Gross, Milton
Abstract : Abstract: Hidradenitis suppurativa is an inflammatory disease associated with subcutaneous nodules/abscesses that occur commonly in the axillary, inguinal, and perineal regions. We describe a case of a 64-year-old man presenting for 18 F-FDG PET/CT for staging of a left vocal cord squamous cell carcinoma. The scan showed uptake in the left vocal cord malignancy and multiple hypermetabolic subcutaneous foci in the right axilla, right buttocks, and scalp in known locations of skin lesions related to hidradenitis suppurativa. This case illustrates an unusual inflammatory cause of 18 F-FDG incidental uptake that should not be mistaken for metastases.